Patterns of contemporary Russo-Syrian relations: A realist interpretation from the Moscow perspectıve - Sakaoğlu, Emre Tunç. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2017., 2017)
The primary aim of this thesis is to shed light on the past, present, and near future of Russian-Syrian relations from a broadly realist perspective, the particular variants of which had been labeled as “old-fashioned” and therefore swept aside without a second thought until recently for their perceived inability to offer a reliable account of contemporary international relations. While trying to reveal the persistent trends, practical necessities, mutual interests, and shared threats underlying the historical evolution of this key bilateral relationship from 1945 till date; the following chapters further explore major fluctuations in the larger international context and the complex interplay between the geopolitical variables of each successive phase under scrutiny. Within this framework, particular attention is paid to the lasting – and apparently, still highly determinative – influence of certain considerations in shaping Russian strategies towards the Greater Middle East. The main reason for this is to bring a convincing answer to widespread questions as to the dynamics behind the transformation of the ongoing Syrian crisis into a geopolitical black hole with utterly destructive repercussions for all parties involved, particularly Syria itself and those countries that lie in its immediate neighborhood. Such an academic inquiry is deemed essential at this stage in time, for the Syrian imbroglio is yet to be resolved. Whereas one needs to diagnose the disease accurately, in as rational a manner as possible, before searching for practical ways to cure it.